Are evidence-based, community-engaged energy balance interventions enough for extremely vulnerable populations?. Issue 5 (17th January 2018) - Schoenberg, Nancy E; Tarasenko, Yelena N; Snell-Rood, Claire
Abstract: Well-documented associations between lifestyle behaviors and disease outcomes necessitate evidence-based health promotion interventions. To enhance potential efficacy and effectiveness, interventionists increasingly respond to community priorities, employ comprehensive theoretical frameworks, invest heavily to ensure cultural fit, implement evidence-based programming, and deploy research gold standards. We describe a project that followed all of these recommended strategies, but did not achieve desired outcomes. This community-based participatory research (CBPR) energy balance (diet and physical activity) intervention, conducted in Appalachian Kentucky among 900+ residents, employed a wait list control cluster randomized design. We engaged faith institutions, took an intergenerational approach, and modified two existing evidence-based interventions to enhance cultural relevance. Despite these efforts, fruit and vegetable consumption and physical activity did not change from baseline to post-test or differed significantly between intervention and wait list control groups. Barriers to engaging in optimal energy balance focused more on motivation and attitude than on structural and material barriers. The complex interplay of psychosocial, structural, and physiological processes offers significant challenges to groups with entrenched health challenges. Abstract : Despite following rigorous intervention standards, our diet and physical activity intervention conducted among 900+ rural Appalachian residents did not change behavior. We explore possible reasons for this lack of change.